Analysis Of Application Geographic Information System Mobile Search High School In Bandar Lampung Equals - Kinasih E S; Sukoco A (Bandar Lampung University (UBL), 2017)
In the current era of modernization is very rapid development of technology that makes all the current facilities have a lot of mobile and web-based. One of the advances in technology today is the presence of Geographic Information System (GIS). Geographic Information System (GIS) is a computer system that has the ability to build, store, manage, and display geographic information references. School is an institution designed for the teaching of students / pupils under the supervision of teachers. Public schools, the school organized by the government, ranging from elementary schools, middle schools,high schools, and colleges. Private schools, the school organized by non-government / private, in the form of weight organizers in the form of educational foundations that until now legal entities education providers is still a draft government regulation.